Survey of agriculture in Latin America and the Caribbean over recent decades (performance indicators in charts and tables) - UN ECLAC. Division of Production, Productivity and (ECLAC [Santiago]CL, 1997)
Contains a summary of the main trends seen in Latin American and Caribbean agriculture over recent decades. Comprises a set of charts and tables illustrating the situation, each of which is accompanied by brief comments. Seeks to provide a general impression of the state of agriculture in the region, and the countries that make it up.